Evolution of EEG Findings in Pontocerebellar Hypoplasia Type 2A: Normal EEG in the First Few Months followed by Abnormal Tracing over the Years - Cohen, Rony; Goldberg-Stern, Hadassah; Kivity, Sara; Halevy, Ayelet; Aharoni, Sharon; Kornreich, Liora; Straussberg, Rachel (Neuropediatrics, 2020)
Pontocerebellar hypoplasia (PCH) is an autosomal recessive neurodevelopmental and neurodegenerative disorder characterized by cerebellar and pontine hypoplasia, progressive microcephaly, and developmental delay. Ten types of PCH have been described; PCH type 2A (PCH2A) due to a mutation in TSEN54 is the most frequent. Seizures have been reported in the large majority of patients. The probability of epilepsy developing increases with age, along with difficulties in differentiating seizures from dyskinetic movements. The aim of the present report was to describe the clinical symptoms and electroencephalogram (EEG) changes over time in three patients of Israeli Arab origin with PCH2A. All three, including two siblings and their first cousin, were homozygous for the TSEN54 p.A304S mutation. The patients demonstrated profound psychomotor retardation, severe spasticity and contractures, choreoathetoid movements, and seizures. The magnetic resonance imaging (MRI) scans and EEGs were reviewed by an experienced neuroradiologist and epileptologist, respectively. The MRI scans revealed a dragonfly-like cerebellar pattern in all patients. Despite the normal early EEG findings, all patients had characteristic features of epilepsy, with tonic seizures starting in the first days to months followed by focal to bilateral tonic–clonic seizures in early childhood which continued to adolescence. In conclusion, patients with PCH2A due to the missense mutation p.A304S in TSEN54 exhibit profound psychomotor delay, movement disorders, and intractable epilepsy. An evolution of EEG abnormalities and seizure semiology occurs over time. Similar to several other genetic epileptic encephalopathies, the normal early EEG tracing does not rule out the later occurrence of epilepsy
Keywords: pontocerebellar hypoplasia; EEG; PCH1A